EVA (ethylene vinyl acetate) film for solar cell packaging - MA DONGFANG; XIE YI; WU WENMING; WANG QINZHEN (2018)
An EVA (ethylene vinyl acetate) film for solar cell packaging contains an EVA copolymer, a silane coupling agent, a crosslinking curing agent, a crosslinking curing accelerator, a stabilizer, an ultraviolet light absorber and a light stabilizer, wherein the silane coupling agent contains vinyl trimethoxysilane and aminopropyltriethoxysilane; the crosslinking curing agent is tert-butyl peroxyformate; the crosslink curing accelerator is triallyl cyanurate; the stabilizer is a macromolecular rare earth complex. According to the EVA film for solar cell packaging, the macromolecular rare earth complex is used as a stabilizer, coordination efficiency of organic ligands is high, and vinyl trimethoxysilane and aminopropyltriethoxysilane are mixed as coupling agents, so that strength of glass is enhanced, and the bonding performance of the packaging film and the glass is also improved. 种用于太阳能电池封装的EVA胶膜，包括：乙烯-醋酸乙烯的共聚物、硅烷偶联剂、交联固化剂、交联固化促进剂、稳定剂、紫外光吸收剂、光稳定剂；其中，硅烷偶联剂包括乙烯基三甲氧基硅烷和氨丙基三乙氧基硅烷；交联固化剂为过氧化甲酸叔丁酯；交联固化促进剂为三聚氰酸三烯丙酯；稳定剂为